Removing isoflavones from modern soyfood: Why and how?. (1st November 2016) - Fernandez-Lopez, Adrian; Lamothe, Valérie; Delample, Mathieu; Denayrolles, Muriel; Bennetau-Pelissero, Catherine
Highlights: Glycosilated isoflavones are water-soluble and adsorbed to legume proteins. They can be separated from proteins by prolonged cooking, simmering or soaking. These traditional practices have no equivalent in modern industrialised processes. The isoflavone:protein ratio in modern soy-food is higher than in traditional food. Our knowledge of the effects of isoflavones is not as detailed as was one thought. Abstract: Estrogenic isoflavones were found, in the 1940s, to disrupt ewe reproduction and were identified in soy-consumers' urine in 1982. This led to controversy about their safety, often supported by current Asian diet measurements, but not by historical data. Traditional Asian recipes of soy were tested while assaying soy glycosilated isoflavones. As these compounds are water-soluble, their concentration is reduced by soaking. Pre-cooking or simmering time-dependently reduces the isoflavone:protein ratio in Tofu. Cooking soy-juice for 15 or 60 min decreases the isoflavone:protein ratios in Tofu from 6.90 to 3.57 and 1.80, respectively (p < 0.001). Traditional Tempeh contains only 18.07% of the original soybean isoflavones (p < 0.001). Soy-juice isoflavones were reduced by ultra-filtration (6.54 vs 1.24 isoflavone:protein; p < 0.001). Soy-protein and isoflavones are dissociated by water rinsing and prolonged cooking, but these have no equivalent in modern processes. As regards human health, a precise definition of the safety level of isoflavone intake requires additional studies.